Catch-up growth in children after acute and protracted diarrhea - Kulik-Rechberger, Beata; Chrząstek-Spruch, Hanna; Furmaga-Jabłońska, Wanda (Anthropological Review, 1997)
One hundred and ten children hospitalized because of acute and protracted diarrhea in the first year of life were followed up for an average period of 13.7 months. Three anthropological parameters were taken into consideration: body height, body weight and head circumference. At the time of the first examination all the parameters measured were significantly decreased but children tend to reestablish normal somatic growth pattern during the rehabilitation period through the acceleration of growth (phenomenon known as “catch-up growth”).